Microorganisms of the San Francisco Sour Dough Bread Process: I. Yeasts Responsible for the Leavening Action - Sugihara, T. F. (1971)
Two hundred isolates from San Francisco sour dough French bread fermentations (40 from each of five different bakeries) were screened by fermentation tests and for their ability to grow in the presence of cycloheximide (Actidione). All of the isolates from four of the bakeries and 70% of those from the fifth were unable to utilize maltose but grew well on other sugars, even in the presence of cycloheximide. The remaining few isolates from the fifth bakery utilized maltose but not galactose and were inhibited by cycloheximide. No bakers' yeast types were found. Sixteen of the maltose-negative and five of the galactose-negative isolates were subjected to more rigorous taxonomic procedures. All of the maltose-negative isolates were identified as asporogenous strains of Saccharomyces exiguus (Torulopsis holmii) and the galactose-negative ones, as S. inusitatus. The predominance of S. exiguus, its vigor in the particular acidic environment of the sour dough, and the correlation of its numbers with the leavening function constitute strong evidence on the role of this organism in the sour dough system.